2020
DOI: 10.21203/rs.3.rs-18259/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oncogenic miR-20b-5p contributes to malignant behaviors of breast cancer stem cells by bidirectionally regulating CCND1 and E2F1

Abstract: Background: Breast cancer is the leading cause of cancer mortality in women worldwide. Therefore, it is of great significance to identify the biological mechanism of tumorigenesis and explore the development of breast cancer to achieve a better prognosis for individuals suffering from breast cancer. MicroRNAs (miRNAs) have become a hot topic in cancer research, but the underlying mechanism of its involvement in cancer remains unclear. Methods: The miRNA profile between breast cancer stem cells (BCSCs, CD44+CD2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Remarkably, previous studies have revealed that the upregulated expressions of CDK1 and CCNB1 are correlated with the worse OS in the basal subtype breast cancer, while CDC20, CCNB1, and CDK1 could act as diagnostic and prognostic markers in breast cancer. Especially, FOXM1 and E2F1 have also been demonstrated to be significantly associated with CSCs in a variety of tumors [50][51][52]. Taken together, we suggested that the mRNAsi-related genes could play very important roles in the occurrence and development as well as prognosis of the basal breast cancer patients.…”
Section: Discussionmentioning
confidence: 63%
“…Remarkably, previous studies have revealed that the upregulated expressions of CDK1 and CCNB1 are correlated with the worse OS in the basal subtype breast cancer, while CDC20, CCNB1, and CDK1 could act as diagnostic and prognostic markers in breast cancer. Especially, FOXM1 and E2F1 have also been demonstrated to be significantly associated with CSCs in a variety of tumors [50][51][52]. Taken together, we suggested that the mRNAsi-related genes could play very important roles in the occurrence and development as well as prognosis of the basal breast cancer patients.…”
Section: Discussionmentioning
confidence: 63%
“…miR-20b-5p, a member of the tumor-related miR-106a/363 cluster, was reported to be frequently dysregulated in numerous human malignancies (9,15,35,36). Mechanistically, miR-20b-5p facilitated the proliferation and inhibited the apoptosis of breast cancer stem cells through the bidirectionally regulation of CCND1 and E2F1 (10). Conversely, miR-20b-5p was reported to inhibit migration, invasion and the cell cycle of colon cancer cells by regulating the CCND1/CDK4/FOXM1 axis (14).…”
Section: Discussionmentioning
confidence: 99%
“…The role of miR-20b-5p in human cancers is controversial. miR-20b-5p has been reported to function as an oncomiR in non-small cell lung cancer (9), breast cancer (10), gastric cancer (11), esophageal cancer (12) and laryngeal squamous cell carcinoma (13), but as a tumor-suppressor miRNA in colon cancer (14) and papillary thyroid carcinoma (15). miR-20b-5p was found to promote the tumor aggression of PCa and can predict aggressive PCa after radical prostatectomy (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of miR-20b attenuates the proportion of cancer stem cells via the direct targeting of Oct4 and MALAT1, critical positive regulators of cancer stem cell stemness [ 73 , 81 , 102 , 103 ], and finally eases tumor regression [ 104 ]. However, miR-20b could promote breast cancer stem cell proliferation and cell cycle [ 64 ]. It indirectly elevates Cyclin D1 and E2F1 mRNA levels and promotes cell proliferation in breast cancer stem cells [ 64 ].…”
Section: Approaches To Determine the Targets Of Mir-20bmentioning
confidence: 99%